O agro é tudo? o direito socioambiental em face da ofensiva legislativa do agronegócio - Libera, Graciele Dalla (My University, 2020)
This is a master's dissertation that aims to verify the legislative offensive in the face of social and environmental rights led by agribusiness, architected by the ruralist bench and supported by the Cultural Industry. The paper addresses the concept of sustainable development as well as agribusiness and the perception of sustainable agribusiness. The concept of agribusiness is outlined, tracing a brief historical regression to the roots of the new rural world. It is understood how this business model is schematized, especially addressing its contradictions. The concept of Cultural Industry is worked on. It is understood the movement of the ruralist bench and its legislative offensive in favor of agribusiness, as well as how the law, in its legislative spectrum, has been managed by agribusiness and its interests. From these considerations, we sought to investigate the direct action of the ruralist bench in the National Congress, analyzing six bills and proposition of parliamentarians that make up this group, invoking the principle of sustainable development, for the benefit of agribusiness, but which will against social and environmental rights. It is concluded that the agribusiness legislative offensive results in a retrogression of the social and environmental law, improperly using the concept of sustainable development, and a violation of the principles of intergenerational equity, prevention, precaution and environmental non-retrogression. The present work constituted as a qualitative research and was studied through two methods, namely dialectical and analytical, adopting techniques of traditional bibliographic review.
Trata-se de uma dissertação de mestrado que pretende verificar a ofensiva legislativa em face dos direitos socioambientais capitaneada pelo agronegócio, arquitetada pela bancada ruralista e amparada pela Indústria Cultural. O trabalho aborda o conceito de desenvolvimento sustentável, bem como, o de agronegócio e da percepção de um agronegócio sustentável. É delineado o conceito de agronegócio, traçando-se uma breve regressão histórica às raízes do novo mundo rural. Compreende-se como esse modelo de negócio esquematiza-se, abordando- se especialmente suas contradições. É trabalhado o conceito de Indústria Cultural. É compreendido o movimento da bancada ruralista e sua ofensiva legislativa em favor do agronegócio, bem como, de que forma o direito, em seu espectro legislativo, vem sendo manejado pelo agronegócio e seus interesses. A partir dessas considerações, buscou-se averiguar a atuação direta da bancada ruralista no Congresso Nacional, analisando-se seis projetos de leis e proposição dos parlamentares que compões esse grupo, invocando o princípio do desenvolvimento sustentável, em benefício do agronegócio, mas que vão de encontro aos direitos socioambientais. Conclui-se que a ofensiva legislativa do agronegócio resulta em retrocesso ao direito socioambiental, utilizando-se indevidamente do conceito de desenvolvimento sustentável, vislumbrando-se violação dos princípios da equidade intergeracional, da prevenção, da precaução e do não-retrocesso ambiental. O presente trabalho constituiu-se como uma pesquisa qualitativa e foi estudada através de dois métodos, a saber, dialético e analítico, adotando-se técnicas de revisão bibliográfica tradicional.
Keywords: Agroindústria; Direito ambiental; Indústria cultural; Desenvolvimento sustentável; Agricultural industries; Environmental law; Cultural industries; Sustainable development